Perinatal stress, brain inflammation and risk of autism-Review and proposal. - Angelidou, Asimenia.; Asadi, Shahrzad.; Alysandratos, Konstantinos-Dionysios.; Karagkouni, Anna.; Kourembanas, Stella.; Theoharides, Theoharis C. (2016)
Background: Autism Spectrum Disorders (ASD) are neurodevelopmental disorders characterized by varying deficits in social interactions, communication, and learning, as well as stereotypic behaviors. Despite the significant increase in ASD, there are few if any clues for its pathogenesis, hampering early detection or treatment. Premature babies are also more vulnerable to infections and inflammation leading to neurodevelopmental problems and higher risk of developing ASD. Many autism "susceptibility" genes have been identified, but "environmental" factors appear to play a significant role. Increasing evidence suggests that there are different ASD endophenotypes.; Keywords: Allergy, Autism, Brain, Inflammation, Mast cells, Prematurity, Stress.; Springer Open.